Preparasi dan Karakterisasi Katalis CoMo/H-Zeolit Y - Rustam Musta (Jurnal Fisika Flux, 2010)
Preparation and characterization of catalyst CoMo/H-zeolite Y has been done. Catalyst was prepared from NH4Y-zeolite then heated 115oC for 1 h to eliminate water then calcined at 550oC for 2 h to evaporate ammonia, produced HY-zeolite (HYZ) sample. Impregnation of CoMo metals on the HYZ sample was done by co-impregnation method, where the HYZ (10 g) was mixed with (NH4)6MO7O24.4H2O in 24 mL aquabidest and 3 mL of ammonia then stirred of 60oC for 2 h. This mixture was then mixed with Co(NO3)2.6H2O in 24 mL aquabidest and 3 mL of ammonia then stirred of 60oC for 2 h. The resulting sample was filtered and dried. The dried sample was then calcined under N2 stream at temperature of 550oC for 2 h, followed by oxidized with O2 then reduced with H2 stream at temperature 400oC for 2 h, respectively produced CoMo/HY catalyst. Characterization of the catalyst included analysis of NH3 groups was done with by infra red spectrofotometry (IR), the crystallinity with Xray diffraction (XRD) and the acidity was calculated with NH3 absorption by gravimetry method, metal content on the catalyst was determined by atomic absorption spectroscopy (AAS). FTIR result of CoMo/HY catalyst showed that disappeared ammonia was after heating. The XRD date indicated the increase of catalyst crystallinity as the following: NH4Y< died NH4Y < HY< CoMo/HY. CoMo/HY catalyst has average acidity = 6,87 mmol/g where as the HY has average acidity = 7,66 mmol/g. The metal content in the HY was 8023 and 7681 ppm, for Co and Mo respectively.